Oleophobic and hydrophobic glass product and application of oleophobic and hydrophobic glass product in cooker panel

By constructing SiO2 coating, coupling group-containing polysiloxane coating and fluoropolysiloxane coating, the existing oleophobic hydrophobic glass products have been solved, and the performance and poor durability of existing oleophobic hydrophobic glass products at high temperatures have been achieved. The high temperature resistance and durability are improved, avoiding the complexity of plasma etching processing.

CN119219342AActive Publication Date: 2024-12-31ZHONGSHAN TAIYUAN GLASS CRAFT PRODUCTS CO LTD

Patent Information

Application Number
CN202411319200.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2024-12-31
Estimated Expiration
2044-09-21

AI Technical Summary

Technical Problem

The existing oleophobic and hydrophobic glass products have reduced performance and poor durability at high temperatures, and require complex plasma etching treatment.

Method used

Using SiO2 coating, coupling group-containing polysiloxane coating and fluoropolysiloxane coating to increase binding force through Si-O-Si chemical bond links, and using polysiloxane as the main chain To enhance high temperature resistance and stability.

Benefits of technology

The high temperature resistance and durability of oleophobic and hydrophobic glass products are significantly improved, and the complexity of plasma etching treatment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219342A_ABST
    Figure CN119219342A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of glass product processing, and particularly relates to an oleophobic and hydrophobic glass product and application thereof in a cooker panel. The preparation method of the oleophobic and hydrophobic glass product comprises the following steps: carrying out cleaning and drying pretreatment on a glass substrate, spraying a silica sol solution, drying at 80-150 DEG C to remove a solvent, heating to 200-400 DEG C, and curing to obtain a SiO2 coating; spraying a polysiloxane solution containing a coupling group on the surface of the SiO2 coating, and drying at 80-150 DEG C to obtain a polysiloxane coating containing the coupling group; and spraying a fluorine-containing polysiloxane prepolymer solution on the surface of the polysiloxane coating, and drying and curing at 90-160 DEG C to obtain the oleophobic and hydrophobic glass product. According to the invention, the SiO2 coating, the polysiloxane coating containing the coupling group and the fluorine-containing polysiloxane coating are sequentially constructed, so that the obtained glass product has good amphiphobic performance and high-temperature-resistant durability, and can be used for manufacturing high-end kitchen range panels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass product processing, and in particular relates to an oleophobic and hydrophobic glass product and an application thereof in a stove panel. Background Art

[0002] Oleophobic and hydrophobic glass refers to a "double-repellent" glass product that has both oleophobic and hydrophobic properties on the glass surface. Because it is not easily contaminated by oil stains and is easy to clean, it is widely used in the manufacture of high-end stove panels.

[0003] At present, the preparation method of "double-repellent" glass products is generally to prepare a layer of oleophobic and hydrophobic coating on the surface of the glass substrate to achieve the "double-repellent" effect. For example, patent CN 113045212 A discloses using a special nano-level oleophobic and hydrophobic coating to treat the glass surface. The nano-level oleophobic and hydrophobic coating uses a silicifying agent·SiO 2 CN 103951278 A discloses a super-hydrophobic and super-oleophobic anti-reflective glass surface layer and a preparation method thereof, firstly through CF 3 / O 2 Plasma etching of the glass body surface to create a submicron rough structure, followed by chemical bonding of a layer of SiO 2 The nanoporous layer is constructed into a double-stage rough glass surface layer with a pendant structure by adding a porogen to adjust the space filling factor, and finally fluorinated to reduce the surface free energy. CN105505087 A discloses a hydrophobic and oleophobic antifouling glass substrate and a production method thereof, wherein the hydrophobic and oleophobic antifouling coating comprises the following components in parts by weight: 70 to 90 parts of perfluoroalkyl ethyl acrylate, 50 to 60 parts of octadecyl acrylate, 30 to 40 parts of octadecyl methacrylate, 10 to 20 parts of dioctadecyl dimethyl ammonium chloride, 30 to 40 parts of polypropylene glycol, 10-30 parts of aluminum tripolyphosphate, 20-50 parts of zinc phosphate, 1 to 5 parts of silicon carbide, 5 to 10 parts of polyamide, 5 to 10 parts of 2,4,6-tris(dimethylaminomethyl)phenol, 1 to 5 parts of surfactant, and 300 to 400 parts of deionized water. The above prior art generally uses fluorocarbon materials to reduce its surface energy to achieve the "double-phobic" effect. However, fluorocarbon materials are generally based on carbon-hydrogen chains, and their carbon-carbon bonds and carbon-hydrogen bonds are easily broken and degraded at high temperatures, resulting in reduced "amphiphobic" performance. At the same time, the binding force between fluorocarbon materials and the glass surface is weak, resulting in poor durability of "amphiphobic" performance. In addition, plasma etching surface treatment is required, and the treatment process is relatively complicated.

[0004] Fluorosilicone materials can be used for the preparation of "double-repellent" coatings because of their low surface properties and high temperature resistance. For example, patent CN118307212A discloses a method for preparing hydrophobic and oleophobic easy-to-clean glass, which is formed by spraying a configured coating composition on the glass surface and curing it. The components of the coating composition include 26% to 30% methyl nonafluorobutyl ether, 62% to 68% ethyl nonafluorobutyl ether, 2% to 3% fluorine-modified silane coupling agent, 1.0% to 1.2% surfactant, 1% to 2% leveling agent, and 0.2% to 0.7% substrate wetting agent. Although the prior art discloses the use of fluorine-modified silane coupling agents to enhance the bonding force with the glass surface, and fluorosilicone oil can be used as a wetting agent, the main component of its coating is a small molecule fluorine-containing compound, the interaction between the components is weak, and it is easy to volatilize or decompose at high temperatures, resulting in poor durability of the "double-repellent" performance. Summary of the invention

[0005] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide a method for preparing an oleophobic and hydrophobic glass product.

[0006] Another object of the present invention is to provide an oleophobic and hydrophobic glass product prepared by the above method.

[0007] Another object of the present invention is to provide application of the above-mentioned oleophobic and hydrophobic glass product in a cooker panel.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing an oleophobic and hydrophobic glass product comprises the following preparation steps:

[0010] (1) After cleaning and drying the glass substrate for pretreatment, the silica sol solution is sprayed on the glass substrate, dried at 80-150°C to remove the solvent, and then heated to 200-400°C for curing to obtain SiO 2 coating;

[0011] (2) In step (1), SiO 2 The polysiloxane solution containing coupling groups is sprayed on the coating surface, and then dried at 80-150° C. to obtain a polysiloxane coating containing coupling groups;

[0012] (3) spraying a fluorinated polysiloxane prepolymer solution on the surface of the polysiloxane coating in step (2), and drying and curing at 90 to 160° C. to obtain an oleophobic and hydrophobic glass product;

[0013] The polysiloxane solution containing coupling groups in step (2) is prepared by the following method:

[0014] The vinyl silane coupling agent and hydrogen-containing silicone oil are mixed evenly under nitrogen protection, the temperature is raised to 60-90° C., a platinum catalyst is added to carry out an addition reaction, and after the addition reaction is completed, an anhydrous dilution solvent is added and mixed to obtain a polysiloxane solution containing a coupling group.

[0015] The preparation of the polysiloxane solution containing coupling groups involves a reaction route such as Figure 1 The polysiloxane containing coupling groups of the present invention has a hydrophobic, oleophobic, high temperature resistant and stable polysiloxane as the main chain, and contains a polysiloxane that can react with SiO 2 The coupling group for coupling and cross-linking with silanol significantly improves the bonding with SiO 2 The coating's bonding strength can be enhanced and the subsequent cross-linking and curing reaction of the fluorinated polysiloxane prepolymer can be participated in to improve the "amphiphobic" effect and durability of the coating.

[0016] Furthermore, the silica sol solution in step (1) preferably has a solid content of 5% to 20% and an average particle size of 50 to 500 nm. The silica sol has good bonding to the glass substrate, and can undergo good coupling reaction with the polysiloxane containing coupling groups, and can construct a surface roughness structure.

[0017] Furthermore, in step (2), the vinyl silane coupling agent is selected from vinyl trimethoxy silane or vinyl triethoxy silane; the hydrogen-containing silicone oil is selected from terminal and / or side hydrogen-containing silicone oil with a hydrogen content of 0.2% to 1.2% (wt%) and an average molecular weight of 2000 to 20000 g / mol; and the mass ratio of the added amount of the vinyl silane coupling agent to the hydrogen-containing silicone oil is 0.2 to 1:1.

[0018] Furthermore, the platinum catalyst in step (2) is chloroplatinic acid or Custer's catalyst (bis(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum).

[0019] Furthermore, the time of the addition reaction in step (2) is 2 to 6 hours.

[0020] Furthermore, the anhydrous dilution solvent in step (2) is ethanol, propanol or isopropanol.

[0021] Furthermore, the fluorinated polysiloxane prepolymer solution in step (3) is prepared by the following method:

[0022] Trifluoropropylmethylcyclotrisiloxane (D3F) is heated to 70-100° C., and then a tetramethylammonium hydroxide catalyst aqueous solution is added and stirred to carry out a ring-opening polymerization reaction. After the ring-opening polymerization reaction is completed, a diluting solvent is added to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution.

[0023] The preparation of the fluorinated polysiloxane prepolymer solution involves the following reactions:

[0024] n / 3[Me(CF 3 CH 2 CH 2 )SiO] 3 +H 2 O→HO[Me(CF 3 CH 2 CH 2 )SiO] n H.

[0025] The fluorinated polysiloxane prepolymer used in the present invention has a fluorocarbon group with low surface energy as a side chain, a hydrophobic and oleophobic, high temperature resistant and stable polysiloxane as a main chain, and contains silanol groups that can undergo cross-linking and curing reactions with the remaining coupling groups, which can significantly improve the "double-phobic" effect and durability of the coating.

[0026] Furthermore, the amount of the tetramethylammonium hydroxide catalyst added is 0.02% to 0.2% of the mass of D3F; and the amount of the water added is 0.1% to 0.5% of the mass of D3F.

[0027] Furthermore, the dilution solvent is methyl isobutyl ketone.

[0028] Furthermore, the drying and curing in step (3) refers to first drying at 90-120° C. to remove the solvent and keeping the temperature to cure for 30-120 minutes, and then heating to 120-160° C. to decompose and remove the tetramethylammonium hydroxide catalyst.

[0029] An oleophobic and hydrophobic glass product is prepared by the method.

[0030] Application of the above-mentioned oleophobic and hydrophobic glass product in a stove panel.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The preparation method of the present invention does not need to use plasma to etch the glass surface. 2 The coating, the polysiloxane coating containing coupling groups and the fluorinated polysiloxane coating are linked by Si-O-Si chemical bonds, which significantly improves the bonding strength of the coating. At the same time, the "double-repellent" coating uses polysiloxane as the main chain, has good high temperature resistance and stability, and the durability of the "double-repellent" performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention provides a reaction scheme for preparing the polysiloxane solution containing coupling groups. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0035] Example 1

[0036] A method for preparing an oleophobic and hydrophobic glass product comprises the following preparation steps:

[0037] (1) After cleaning and drying the glass substrate for pretreatment, a silica sol aqueous solution with a solid content of 5% and an average particle size of 50 nm was sprayed on the substrate, dried at 100°C for 30 seconds to remove the solvent, and then heated to 200°C for curing for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0038] (2) Vinyl trimethoxysilane and a terminal hydrogenated silicone oil with a hydrogen content of 0.36% (wt%) and an average molecular weight of 12000 g / mol were mixed uniformly under nitrogen protection, the mass ratio of the amount of vinyl trimethoxysilane added to the hydrogenated silicone oil being 0.2:1, the temperature was raised to 80° C., a Custer catalyst with a mass concentration of 0.01% was added to carry out an addition reaction for 3 hours, and after the addition reaction was completed, 2 times the mass of isopropanol solvent was added and mixed uniformly to obtain a polysiloxane solution containing a coupling group. In step (1), SiO 2 The surface of the coating is sprayed with the polysiloxane solution containing coupling groups, and dried at 100° C. to obtain a polysiloxane coating containing coupling groups with a thickness of about 10 μm.

[0039] (3) D3F is heated to 85°C, and then a tetramethylammonium hydroxide catalyst aqueous solution is added (the amount of tetramethylammonium hydroxide catalyst added is 0.05% of the mass of D3F; the amount of water added is 0.2% of the mass of D3F) and stirred and mixed to carry out a ring-opening polymerization reaction until the system viscosity increases to 1500-2000mPa·s and the reaction is completed, and then 1 times the mass of methyl isobutyl ketone solvent is added to dilute to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution. The above-mentioned fluorinated polysiloxane prepolymer solution is sprayed on the surface of the polysiloxane coating in step (2), first dried at 105°C to remove the solvent and kept warm for curing reaction for 90 minutes, and then heated to 150°C to decompose and remove the tetramethylammonium hydroxide catalyst to obtain an oleophobic and hydrophobic glass product with a fluorinated polysiloxane film thickness of about 10μm.

[0040] The oleophobic and hydrophobic glass product obtained in this embodiment is subjected to oleophobic and hydrophobic performance test (contact angle test using hexadecane droplets and water droplets respectively). The results show that the surface contact angle of the hexadecane droplets is 125°, and the surface contact angle of the water droplets is 142°; after high temperature treatment at 240°C for 2h, the surface contact angle of the hexadecane droplets is 118°, and the surface contact angle of the water droplets is 135°; after rubbing back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of the hexadecane droplets is 101°, and the surface contact angle of the water droplets is 117°. It can be seen from the above results that the glass product obtained by the present invention has excellent oleophobic and hydrophobic properties, and has good high temperature resistance and durability.

[0041] Example 2

[0042] A method for preparing an oleophobic and hydrophobic glass product comprises the following preparation steps:

[0043] (1) After cleaning and drying the glass substrate, a silica sol aqueous solution with a solid content of 10% and an average particle size of 100 nm was sprayed on the substrate, dried at 120°C for 30 seconds to remove the solvent, and then heated to 250°C for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0044] (2) Vinyl trimethoxysilane and a terminal side-group hydrogenated silicone oil with a hydrogen content of 0.5% (wt%) and an average molecular weight of 9600 g / mol were mixed uniformly under nitrogen protection, the mass ratio of the amount of vinyl trimethoxysilane added to the hydrogenated silicone oil being 0.4:1, the temperature was raised to 80° C., a Custer catalyst with a mass concentration of 0.01% was added to carry out an addition reaction for 4 hours, and after the addition reaction was completed, 1.5 times the mass of isopropanol solvent was added and mixed uniformly to obtain a polysiloxane solution containing a coupling group. In step (1), the SiO 2 The polysiloxane solution containing coupling groups is sprayed on the surface of the coating, and dried at 120° C. to obtain a polysiloxane coating containing coupling groups with a thickness of about 10 μm.

[0045] (3) D3F is heated to 90°C, and then a tetramethylammonium hydroxide catalyst aqueous solution is added (the amount of tetramethylammonium hydroxide catalyst added is 0.05% of the mass of D3F; the amount of water added is 0.2% of the mass of D3F) and stirred and mixed to carry out a ring-opening polymerization reaction until the system viscosity increases to 1500-2000mPa·s and the reaction is completed, and then 1 times the mass of methyl isobutyl ketone solvent is added to dilute to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution. The above-mentioned fluorinated polysiloxane prepolymer solution is sprayed on the surface of the polysiloxane coating in step (2), first dried at 105°C to remove the solvent and kept warm for curing reaction for 90 minutes, and then heated to 150°C to decompose and remove the tetramethylammonium hydroxide catalyst to obtain an oleophobic and hydrophobic glass product with a fluorinated polysiloxane film thickness of about 10μm.

[0046] The oleophobic and hydrophobic glass product obtained in this embodiment is tested for oleophobic and hydrophobic properties. The surface contact angle of the hexadecane droplet is 128°, and the surface contact angle of the water droplet is 145°; after being treated at 240°C for 2h, the surface contact angle of the hexadecane droplet is 115°, and the surface contact angle of the water droplet is 136°; after being rubbed back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of the hexadecane droplet is 105°, and the surface contact angle of the water droplet is 122°. It can be seen from the above results that the glass product obtained by the present invention has excellent oleophobic and hydrophobic properties, and has good high temperature resistance and durability.

[0047] Example 3

[0048] A method for preparing an oleophobic and hydrophobic glass product comprises the following preparation steps:

[0049] (1) After cleaning and drying the glass substrate, a silica sol aqueous solution with a solid content of 15% and an average particle size of 200 nm was sprayed on the substrate, dried at 130°C for 30 seconds to remove the solvent, and then heated to 300°C for curing for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0050] (2) Vinyl triethoxysilane and a side-group hydrogenated silicone oil with a hydrogen content of 0.72% (wt%) and an average molecular weight of 7500 g / mol were mixed uniformly under nitrogen protection, the mass ratio of the amount of vinyl triethoxysilane added to the hydrogenated silicone oil being 0.6:1, the temperature was raised to 85° C., a chloroplatinic acid catalyst with a mass concentration of 0.02% was added for an addition reaction for 4 hours, and after the addition reaction was completed, 1.5 times the mass of isopropanol solvent was added and mixed uniformly to obtain a polysiloxane solution containing a coupling group. In step (1), SiO 2 The polysiloxane solution containing coupling groups is sprayed on the surface of the coating, and dried at 130° C. to obtain a polysiloxane coating containing coupling groups with a thickness of about 10 μm.

[0051] (3) D3F is heated to 95°C, and then a tetramethylammonium hydroxide catalyst aqueous solution is added (the amount of tetramethylammonium hydroxide catalyst added is 0.05% of the mass of D3F; the amount of water added is 0.2% of the mass of D3F) and stirred and mixed to carry out a ring-opening polymerization reaction until the system viscosity increases to 1500-2000mPa·s and the reaction is completed, and then 1 times the mass of methyl isobutyl ketone solvent is added to dilute to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution. The above-mentioned fluorinated polysiloxane prepolymer solution is sprayed on the surface of the polysiloxane coating in step (2), first dried at 105°C to remove the solvent and kept warm for curing reaction for 90 minutes, and then heated to 150°C to decompose and remove the tetramethylammonium hydroxide catalyst to obtain an oleophobic and hydrophobic glass product with a fluorinated polysiloxane film thickness of about 10μm.

[0052] The oleophobic and hydrophobic glass product obtained in this embodiment is tested for oleophobic and hydrophobic properties. The surface contact angle of the hexadecane droplet is 124°, and the surface contact angle of the water droplet is 140°; after being treated at 240°C for 2h, the surface contact angle of the hexadecane droplet is 112°, and the surface contact angle of the water droplet is 131°; after being rubbed back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of the hexadecane droplet is 108°, and the surface contact angle of the water droplet is 125°. It can be seen from the above results that the glass product obtained by the present invention has excellent oleophobic and hydrophobic properties, and has good high temperature resistance and durability.

[0053] Example 4

[0054] A method for preparing an oleophobic and hydrophobic glass product comprises the following preparation steps:

[0055] (1) After cleaning and drying the glass substrate, a silica sol aqueous solution with a solid content of 20% and an average particle size of 500 nm was sprayed on the substrate, dried at 140°C for 30 seconds to remove the solvent, and then heated to 400°C for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0056] (2) Vinyl triethoxysilane and a side-group hydrogenated silicone oil with a hydrogen content of 0.9% (wt%) and an average molecular weight of 4000 g / mol were mixed uniformly under nitrogen protection, the mass ratio of the amount of vinyl triethoxysilane added to the hydrogenated silicone oil being 0.8:1, the temperature was raised to 90° C., a chloroplatinic acid catalyst with a mass concentration of 0.02% was added to carry out an addition reaction for 4 hours, and after the addition reaction was completed, 1 times the mass of isopropanol solvent was added and mixed uniformly to obtain a polysiloxane solution containing a coupling group. In step (1), SiO 2 The polysiloxane solution containing coupling groups is sprayed on the surface of the coating, and dried at 140° C. to obtain a polysiloxane coating containing coupling groups with a thickness of about 10 μm.

[0057] (3) D3F is heated to 95°C, and then a tetramethylammonium hydroxide catalyst aqueous solution is added (the amount of tetramethylammonium hydroxide catalyst added is 0.05% of the mass of D3F; the amount of water added is 0.2% of the mass of D3F) and stirred and mixed to carry out a ring-opening polymerization reaction until the system viscosity increases to 1500-2000mPa·s and the reaction is completed, and then 1 times the mass of methyl isobutyl ketone solvent is added to dilute to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution. The above-mentioned fluorinated polysiloxane prepolymer solution is sprayed on the surface of the polysiloxane coating in step (2), first dried at 105°C to remove the solvent and kept warm for curing reaction for 90 minutes, and then heated to 150°C to decompose and remove the tetramethylammonium hydroxide catalyst to obtain an oleophobic and hydrophobic glass product with a fluorinated polysiloxane film thickness of about 10μm.

[0058] The oleophobic and hydrophobic glass product obtained in this embodiment is tested for oleophobic and hydrophobic properties. The surface contact angle of the hexadecane droplet is 120°, and the surface contact angle of the water droplet is 147°; after being treated at 240°C for 2h, the surface contact angle of the hexadecane droplet is 109°, and the surface contact angle of the water droplet is 128°; after being rubbed back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of the hexadecane droplet is 110°, and the surface contact angle of the water droplet is 131°. It can be seen from the above results that the glass product obtained by the present invention has excellent oleophobic and hydrophobic properties, and has good high temperature resistance and durability.

[0059] Comparative Example 1

[0060] A method for preparing an oleophobic and hydrophobic glass product, compared with Example 1, does not contain the polysiloxane coating containing a coupling group in step (2), comprising the following preparation steps:

[0061] (1) After cleaning and drying the glass substrate for pretreatment, a silica sol aqueous solution with a solid content of 5% and an average particle size of 50 nm was sprayed on the substrate, dried at 100°C for 30 seconds to remove the solvent, and then heated to 200°C for curing for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0062] (2) D3F is heated to 85°C, and then a tetramethylammonium hydroxide catalyst aqueous solution is added (the amount of tetramethylammonium hydroxide catalyst added is 0.05% of the mass of D3F; the amount of water added is 0.2% of the mass of D3F) and the mixture is stirred and mixed to carry out a ring-opening polymerization reaction until the system viscosity increases to 1500-2000 mPa·s and the reaction is completed, and then 1 times the mass of methyl isobutyl ketone solvent is added to dilute, to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution. In step (1), SiO 2 The fluorinated polysiloxane prepolymer solution was sprayed on the coating surface, dried at 105°C to remove the solvent and kept warm for 90 minutes for curing reaction, and then heated to 150°C to decompose and remove the tetramethylammonium hydroxide catalyst to obtain an oleophobic and hydrophobic glass product with a fluorinated polysiloxane film layer thickness of about 20 μm.

[0063] The oleophobic and hydrophobic performance test results of the oleophobic and hydrophobic glass products obtained in this comparative example showed that the surface contact angle of hexadecane droplets was 117°, and the surface contact angle of water droplets was 136°; after high-temperature treatment at 240°C for 2h, the surface contact angle of hexadecane droplets was 105°, and the surface contact angle of water droplets was 123°; after rubbing back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of hexadecane droplets was 89°, and the surface contact angle of water droplets was 101°.

[0064] It can be seen from the above results that the present invention uses the polysiloxane coating containing coupling groups as the connecting layer to achieve the bonding between fluorinated polysiloxane and SiO 2 Good bonding of the coating improves the high temperature resistance and durability of the coating.

[0065] Comparative Example 2

[0066] A method for preparing an oleophobic and hydrophobic glass product, compared with Example 1, does not contain the fluorine-containing polysiloxane coating of step (3), comprising the following preparation steps:

[0067] (1) After cleaning and drying the glass substrate for pretreatment, a silica sol aqueous solution with a solid content of 5% and an average particle size of 50 nm was sprayed on the substrate, dried at 100°C for 30 seconds to remove the solvent, and then heated to 200°C for curing for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0068] (2) Vinyl trimethoxysilane and a terminal hydrogenated silicone oil with a hydrogen content of 0.36% (wt%) and an average molecular weight of 12000 g / mol were mixed uniformly under nitrogen protection, the mass ratio of the amount of vinyl trimethoxysilane added to the hydrogenated silicone oil being 0.2:1, the temperature was raised to 80° C., a Custer catalyst with a mass concentration of 0.01% was added to carry out an addition reaction for 3 hours, and after the addition reaction was completed, 2 times the mass of isopropanol solvent was added and mixed uniformly to obtain a polysiloxane solution containing a coupling group. In step (1), SiO 2 The surface of the coating is sprayed with the polysiloxane solution containing coupling groups, and dried at 100° C. to obtain a polysiloxane coating containing coupling groups with a thickness of about 20 μm.

[0069] The oleophobic and hydrophobic performance test results of the oleophobic and hydrophobic glass products obtained in this comparative example showed that the surface contact angle of hexadecane droplets was 97°, and the surface contact angle of water droplets was 116°; after high-temperature treatment at 240°C for 2h, the surface contact angle of hexadecane droplets was 90°, and the surface contact angle of water droplets was 108°; after rubbing back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of hexadecane droplets was 90°, and the surface contact angle of water droplets was 106°.

[0070] It can be seen from the above results that the oleophobic and hydrophobic properties of glass products can be significantly improved by preparing the fluorinated polysiloxane coating in the present invention.

[0071] Comparative Example 3

[0072] A method for preparing an oleophobic and hydrophobic glass product, compared with Example 1, uses a fluorosilane coupling agent and a fluorocarbon surfactant to replace the polysiloxane coating containing a coupling group and the fluorine-containing polysiloxane coating, comprising the following preparation steps:

[0073] (1) After cleaning and drying the glass substrate for pretreatment, a silica sol aqueous solution with a solid content of 5% and an average particle size of 50 nm was sprayed on the substrate, dried at 100°C for 30 seconds to remove the solvent, and then heated to 200°C for curing for 15 minutes to obtain a SiO2 film with a thickness of about 30 μm. 2 coating.

[0074] (2) Spray a 33% trifluoropropyltrimethoxysilane isopropanol solution onto the SiO 2 The coating surface was dried at 100°C to obtain a silane coating containing coupling groups with a thickness of about 10 μm.

[0075] (3) Spraying a fluorocarbon surfactant solution (DuPont Zonyl 9360) onto the surface of the silane coating in step (2), and drying at 105° C. to form a film, thereby obtaining an oleophobic and hydrophobic glass product having a fluorocarbon surfactant film layer thickness of about 10 μm.

[0076] The oleophobic and hydrophobic performance test results of the oleophobic and hydrophobic glass products obtained in this comparative example showed that the surface contact angle of hexadecane droplets was 102°, and the surface contact angle of water droplets was 123°; after high-temperature treatment at 240°C for 2h, the surface contact angle of hexadecane droplets was 74°, and the surface contact angle of water droplets was 80°; after rubbing back and forth with 0# steel wool with a load of 1kg for 7500 times, the surface contact angle of hexadecane droplets was 81°, and the surface contact angle of water droplets was 92°.

[0077] It can be seen from the above results that the combination of the polysiloxane coating containing coupling groups and the fluorine-containing polysiloxane coating used in the present invention can significantly improve the oleophobic and hydrophobic properties, high temperature resistance and durability compared to conventional fluorosilane coupling agents and fluorocarbon surfactants.

[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an oleophobic and hydrophobic glass product, characterized in that: The method comprises the following preparation steps: (1) After cleaning and drying the glass substrate for pretreatment, a silica sol solution is sprayed on the substrate, the substrate is dried at 80 to 150° C. to remove the solvent, and then the substrate is heated to 200 to 400° C. to be cured to obtain a SiO2 coating; (2) spraying a polysiloxane solution containing coupling groups on the surface of the SiO2 coating in step (1), and drying at 80 to 150° C. to obtain a polysiloxane coating containing coupling groups; (3) spraying a fluorinated polysiloxane prepolymer solution on the surface of the polysiloxane coating in step (2), and drying and curing at 90 to 160° C. to obtain an oleophobic and hydrophobic glass product; The polysiloxane solution containing coupling groups in step (2) is prepared by the following method: The vinyl silane coupling agent and hydrogen-containing silicone oil are mixed evenly under nitrogen protection, the temperature is raised to 60-90° C., a platinum catalyst is added to carry out an addition reaction, and after the addition reaction is completed, an anhydrous dilution solvent is added and mixed to obtain a polysiloxane solution containing a coupling group.

2. The method for preparing an oleophobic and hydrophobic glass product according to claim 1, characterized in that: The silica sol solution in step (1) is a silica sol aqueous solution with a solid content of 5% to 20% and an average particle size of 50 to 500 nm.

3. The method for preparing an oleophobic and hydrophobic glass product according to claim 1, characterized in that: The vinyl silane coupling agent in step (2) is selected from vinyl trimethoxy silane or vinyl triethoxy silane; the hydrogen-containing silicone oil is selected from terminal and / or side group hydrogen-containing silicone oil with a hydrogen content of 0.2% to 1.2% and an average molecular weight of 2000 to 20000 g / mol; the mass ratio of the added amount of the vinyl silane coupling agent to the hydrogen-containing silicone oil is 0.2 to 1:

1.

4. The method for preparing an oleophobic and hydrophobic glass product according to claim 1, characterized in that: The platinum catalyst in step (2) is chloroplatinic acid or Custer's catalyst; the time of the addition reaction is 2 to 6 hours; and the anhydrous dilution solvent is ethanol, propanol or isopropanol.

5. The method for preparing an oleophobic and hydrophobic glass product according to claim 1, characterized in that: The fluorinated polysiloxane prepolymer solution in step (3) is prepared by the following method: The D3F is heated to 70-100° C., and then a tetramethylammonium hydroxide catalyst aqueous solution is added and stirred to carry out a ring-opening polymerization reaction. After the ring-opening polymerization reaction is completed, a diluting solvent is added to obtain a hydroxyl-terminated fluorinated polysiloxane prepolymer solution.

6. The method for preparing an oleophobic and hydrophobic glass product according to claim 5, characterized in that: The added amount of the tetramethylammonium hydroxide catalyst is 0.02% to 0.2% of the mass of D3F; the added amount of the water is 0.1% to 0.5% of the mass of D3F.

7. The method for preparing an oleophobic and hydrophobic glass product according to claim 5, characterized in that: The dilution solvent is methyl isobutyl ketone.

8. The method for preparing an oleophobic and hydrophobic glass product according to claim 5, characterized in that: The drying and curing in step (3) refers to first drying at 90-120° C. to remove the solvent and keeping the temperature to cure for 30-120 minutes, and then heating to 120-160° C. to decompose and remove the tetramethylammonium hydroxide catalyst.

9. An oleophobic and hydrophobic glass product, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

10. Use of the oleophobic and hydrophobic glass product according to claim 9 in a cooker panel.

Citation Information

Patent Citations

  • Super-hydrophobic and oleophobic composite coating and preparation method thereof

    CN104745045A

  • Hydrophobic composite material, preparation method, use thereof and glass containing same

    CN108996915A

  • Preparation method of super hydrophobic and oleophobic silica solution

    CN109401373A

  • Hydrophobic and oleophobic coating and preparation method thereof

    CN117987007A

  • Grafted polymers as oleophobic or hydrophobic coatings

    US20150004861A1

Cited By

  • High-temperature-resistant scratch-resistant easy-to-clean glass product and preparation method thereof

    CN119264810A

  • High-temperature-resistant, scratch-resistant, and easy-to-clean glass product and preparation method thereof

    CN119264810B